Vern Yip's vacation at home : design ideas for creating your everyday getaway - Yip, Vern (Running Press, 2019)
We've all heard that our home should be our sanctuary, but most of us fall short of that ideal. Too often, the reality is that our homes are just another place for stress and work. Now trusted HGTV and TLC interior designer Vern Yip is here to guide us on confidently creating a home where we can instantly feel relaxed and rejuvenated, while also reflecting our individual style and needs. In this lush, beautifully illustrated book, Vern shares the tips, tricks, and design principles that 5-star resorts and hotels use to help guests get into vacation mode, and shows how we can duplicate that sense of ease and relaxation (while fitting into our personal design flair). He also opens the doors to some of his clients' homes to show you how these key design principles can vary with different styles, tastes, and locations. With Vern's reassuring tone and clear, easy steps, readers can create spaces that can make everyday feel like vacation!